2021
DOI: 10.31983/manr.v3i2.7630
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Whatsapp Video-Based Education About Childbirth on the Knowledge and Attitudes of Third Trimester Pregnant Women

Abstract: Background: One of efforts to reduce maternal and child mortality is childbirth assistance by health workers. In reality in the field the community do not fully trust health workers as childbirth helpers, they prefer traditional birth attendance as childbirth helpers. There is still childbirth assistance by non-health workers (traditional birth attendance), therefore the provision of communication, information and education (CIE) must still be provided in various ways including through social media, one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Wikansari et al [34] showed that pregnant women use WhatsApp and Instagram to receive self-care processes at home, of which WhatsApp is mostly used by pregnant women. Sulastri et al [46] showed that WhatsApp is a good tool for providing health information related to childbirth preparation. Hickhs et al [47] also introduced Facebook as the most used social network to receive or access information about pregnancy and childbirth.…”
Section: Discussionmentioning
confidence: 99%
“…Wikansari et al [34] showed that pregnant women use WhatsApp and Instagram to receive self-care processes at home, of which WhatsApp is mostly used by pregnant women. Sulastri et al [46] showed that WhatsApp is a good tool for providing health information related to childbirth preparation. Hickhs et al [47] also introduced Facebook as the most used social network to receive or access information about pregnancy and childbirth.…”
Section: Discussionmentioning
confidence: 99%